Coaching Klinik Psikologi & Pendidikan Agama Islam Sebagai Upaya Preventif Perilaku Kenakalan Remaja di Yayasan Al-Fatimah - Khoirotus Silfiyah; Aya Mamlu’ah; Sitti Atiyatul Mahfudoh; Siti Ulin Ni’mah Muzayyamah (LP3M IAIFA Kediri, 2025)
Psychological coaching and Islamic religious education represent one form of community service motivated by several issues occurring at the Al Fatimah Foundation in Bojonegoro. These issues include behavioral deviations among female students (santri), such as lying, using inappropriate (negative) language, leaving the boarding school without permission, and violating the established rules and norms. Ideally, an Islamic boarding school (pesantren) is a place where individuals reside to deepen their knowledge of religion and other disciplines. However, in reality, behavioral deviations have been observed that negatively impact both the psychological and spiritual well-being of the students. This community service activity was carried out at the Al Fatimah Islamic Boarding School Foundation, involving 36 participants who are female teachers (ustadzah) from various educational levels: RA (Kindergarten), MI Plus (Elementary), SMA Plus (High School), and Madin Unggulan (Islamic Supplementary School). The method employed was the Asset-Based Community Development (ABCD) approach, which focuses on developing the existing potential of the institution. The first focus of the activity was psychological clinical coaching, aimed at equipping the teachers with preventive strategies and psychological understanding of the positive and negative impacts of students’ behaviors. The second focus centered on Islamic religious education, offering a comprehensive explanation from the perspective of Islamic teachings and law regarding the consequences of deviant behavior. The results of the mentoring program showed that 85% of the psychological and Islamic education coaching was understood and could be effectively applied by the participants to guide adolescent students, particularly at the Al Fatimah Islamic Boarding School Foundation in Bojonegoro.